Patient Citizens, Immigrant Mothers : Mexican Women, Public Prenatal Care, and the Birth Weight Paradox - Gálvez, Alyshia (Book collections on Project MUSE., 2011)
According to the Latina health paradox, Mexican immigrant women have less complicated pregnancies and more favorable birth outcomes than many other groups, in spite of socioeconomic disadvantage. In Patient Citizens, Immigrant Mothers, Alyshia G̀lvez takes us from inside the halls of a busy metropolitan hospital's public prenatal clinic to the Oaxaca and Puebla states in Mexico to look at the ways Mexican women manage their pregnancies. The book is both a migration story and a look at the ways that immigrants are received by our medical institutions and by our society.